VALIDATION OF SIMPLE UV-VIS SPECTROPHOTOMETRY METHOD BASED ON ICH Q2 (R1) GUIDELINE FOR THE ANALYSIS OF SODIUM HYPOCHLORITE USING RHODAMINE B - Miftakul Munir; Siska Febriana; Witarti Witarti (LIPI Press, Anggota IKAPI, 2017)
Sodium hypochlorite (NaOCl) has many functions, one of them is as an oxidizing agent in 99Mo/99mTc generator based on ZBM. However, the NaOCl has cytotoxic effect which can harm human body. Hence, there is a need for analytical procedure for its determination. This study describes the validation parameters given by International Conference on Harmonisation (ICH) Q2(R1) to ensure that the UV-Vis spectrophotometric method using rhodamine B is suitable for determination of NaOCl concentration. This method was validated in respect of linearity, specificity and sensitivity. Whereas, the parameter of accuracy and precision is need to be developed to meet the acceptable criteria. The method resulted in a range of linearity, coefficient of correlation and limit of quantification of 0.2 - 4.8 mg L-1, 0.996 and 0.2 mg L-1, respectively.